N-heterocyclic phosphenium and phosphido nickel complexes supported by a pincer ligand framework. Issue 5 (14th October 2015) - Evers-McGregor, Deirdra A.; Bezpalko, Mark W.; Foxman, Bruce M.; Thomas, Christine M.
Abstract : A tridentate ligand framework containing a central N-heterocyclic phosphenium cation (NHP + ) has been coordinated to nickel. Among the compounds reported is a series of [(PPP)Ni]2 0/+/2+ dimers in three different redox states. Abstract : A chelating diphosphine ligand with a central N-heterocyclic phosphenium cation (NHP + ) has been used to explore the coordination chemistry of NHPs with nickel. Treatment of the chlorophosphine precursor [PPP]Cl (1 ) with stoichiometric Ni(COD)2 affords (PPP)NiCl (8 ), which is best described as a Ni II /NHP − phosphido complex formed via oxidative addition of the P–Cl bond. In contrast, treating [PPP]Cl (1 ) with excess Ni(COD)2 results in a mixture of the trimetallic complex (PPP)2 Ni3 Cl2 (9 ) and the reduced NHP-bridged dimer [(PPP)Ni]2 (10 ). Compound9 is found to be a Ni II Ni II Ni 0 complex in which the two NHP ligands act as bridging NHP − phosphidos, while complex10 is a Ni I Ni I complex that is highly delocalized throughout the symmetric Ni2 P2 core. In contrast, the reaction of [PPP][PF6 ] (11 ) with Ni(COD)2 affords an asymmetrically-bridged dication [(PPP)Ni]2 [PF6 ]2 (12 ), which is found to contain two bridging NHP + cations bridging two Ni 0 centers. Comproportionation of10 and12 affords monocationic [(PPP)Ni]2 [PF6 ] (13 ), completing the redox series. Nickel complexes8–10 and12 are largely similar to their Pd and Pt analogues, but a paramagnetic monocation such as13 was not observed in the Pd and Pt case. Computational studies lend further insight into the electronic structure and bonding in complexes8–10 and12–13, and further support the potential redox non-innocent properties of NHP ligands.